Sobre heróis, coronéis e operários: notas acerca da disciplina do corpo e da ortopedia da alma em uma companhia têxtil de Minas Gerais - Rafael Diogo Pereira (2014)
In this study, I sought to address subjects and their inherent power relations, casting my gaze over their statements and their resulting effects of truth. In short, subjects, power and truth are central themes for this study and will be worked inseparably intertwined and throughout the analytical path. My intention was to bring out the tangle of power relations present in the trajectory of these subjects crossing several planes such as family and work. Subjects who, at some point, had their existence crossed by the trajectory of one of the earliest textile industries of Brazil: Cia Cedro & Cachoeira. Founded in 1872, this company spans more than 140 years of our history, bringing with it a range of discourses and statements able to tell us much about the practices that marked the daily life of their factories and their workers' villages. In addition to considering the statements present in the late nineteenth century, gradually I covered dispersed speeches by numerous discursive events, going from the micro to the macro powers, of the foundation to the present day. In order to access the complexity of the processes of formation of these subjects and analyze the regimes of truth that permeated their organizational space and social reality, it was necessary to work with a different conception of power distinct from their orthodox or traditional view. Thus, with regard to the theoretical architecture of this work, I sought elements derived from the works of Michel Foucault, which analyze the power under the relational perspective, without merely reducing it to their negative or repressive traits. This influential French philosopher presents a concept particularly relevant to my intent by allowing the analysis of the power from a relational field of forces, viscerally marked by the emergence of discourses of each period. On the other hand, working with Foucault's thinking also implies recognizing his impact on the most basic aspect of any study. That is, in order not to operate in an inconsistent manner with the foundations of this thinker, I sought to embrace the Foucauldian perspective not only in theory, but also in their ontological, epistemological and analytical. From the analytical point of view, the effort was directed towards the artesanal contruction of an analytical proposal based on his conception of speech and power. The result of this mix of effort and wandering is what awaits us in the following pages.